Including Value Education in Tertiary Level: What Bangladesh Think - Faisal, Rajib Ahmed; Akther, Jarin (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2020)
Bangladesh is a country with numerous number of cultural, social and religious diversity. Such in a pluralist society, it is not easy to identify the common values to be taught. Therefore it is necessary to develop pupils’ values to show respect to others cultures and promote mutual tolerance and understanding through Value Education (VE). The purpose of the research was to explore teachers’ and students’ opinion to include VE as a course in higher education level in Bangladesh. It was a qualitative study and data was collected from the university teachers and students via semi-structured interview. In this study it has been found that religion is a sensitive issue to be taught in VE class which may cause conflict between teacher and students. Participants suggested that VE contents should be practical rather than be theoretical only. One of the challenges to include VE course was the influence of job market economy and because of it students would consider the course as a burden, not to fit for having jobs in future. One of the recommendations of this research was that VE teachers should be open, liberal, and respectful to students’ believe to manage the classroom conflict.